Employees at work in Dow Agricultural Chemical Research Laboratory - Dow Chemical Company (1941)
General view of two employees at work in a Dow Chemical Company Agricultural Chemical Research and Development Laboratory facility. Per an article in the August 1941 edition of the Dow Diamond, the department was responsible for studying the diseases of living plants, the effects of parasites, and the study and testing of insecticides, fungicides, and fumigants. The employee seated at the table on the right-hand side is identified as "Dieter."
Keywords: Agricultural chemicals; Employees; Chemical industry; Plants; Laboratories; Dow Chemical Company; Corporations; Agricultural chemistry; Scientific apparatus and instruments